Challenges In Learning English Online During the Covid-19 Pandemic in Non-English Department Students - Utami, Ketut Herya Darma; Kresnawati, Luh Putu Dian; Rismadewi, Ni Wayan Monik (Universitas Pendidikan Ganesha, 2022)
Several challenges are faced in implementing online learning, such as being less familiar with online learning. This study aimed to analyze the challenges faced by students majoring in Non-English Education in online English learning during the Covid 19 pandemic. The research design used was descriptive and qualitative. Data were obtained from 412 students majoring in Non-English Education. Data collection techniques used are questionnaires and interviews. The questionnaire was made in a google form and filled out by respondents online, while the structured interview technique was carried out using the Zoom application. Data analysis activities include data reduction, presentation, and conclusion drawing/verification. The results showed that the biggest challenge came from students' psychological problems, such as; limited opportunities to interact with lecturers and colleagues directly, lack of feedback or clarification from lecturers or colleagues, more independent learning to solve problems, and lack of student-centered learning activities. Another big challenge is technical problems such as an unsupported internet network, limited internet access, or an unstable internet connection.